Competency Evaluation of Automotive Vocational School Graduates - Bambang Sudarsono (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the competencies possessed by graduates of SMK Otomotif students based on the point of view of the head of a car repair mechanic. The approach used in this research is descriptive with the research subjects of the chief mechanics of automotive repair shops in Purworejo Regency, totaling 15 mechanics. The instrument used was a questionnaire and analyzed descriptively. Before being used, the questionnaire was validated by an automotive education and engineering expert. The results showed that the highest percentage of achievement was found in social competence of 82.77%, personality competence of 77.78% and professional competence of 63.75%.